Multifaceted role of synbiotics as nutraceuticals, therapeutics and carrier for drug delivery. (1st December 2022) - Khursheed, Rubiya; Gulati, Monica; Wadhwa, Sheetu; Vishwas, Sukriti; Sharma, Deep Shikha; Corrie, Leander; Alam, Aftab; Alnasser, Sulaiman Mohammed; Aba Alkhayl, Faris F.; Parveen, Zeenat; Nammi, Srinivas; Chellappan, Dinesh Kumar; et al.
Abstract: Synbiotics, are a combination of probiotics and prebiotics. They play an important role in metabolizing different nutritional substrates and thus helps in the maintenance of human health. Any disbalance in the gut microflora, known as dysbiosis, is known to lead to a number of diseased conditions. It can be reverted by the administration of synbiotics. Present review highlights various mechanistic pathways through which synbiotics act as therapeutics. The dual role of synbiotics as nutraceutical and excipient in developing oral formulations are entailed with case studies. The findings entailed that there exist numerous studies on prebiotics as well as probiotics have been carried out to show their effects in several diseases. However, the concept of combining together them for prevention and treatment of various pathological conditions accruing from dysbiosis is relatively new. Synbiotics, however, face challenge of low stability during their sojourn in the GIT, which is generally overcome by various encapsulation techniques. Various studies also showed potential role of synbiotics in drug delivery. However, it is an emerging area and lacks clinical correlation. It is important to focus on clinical trials of formulations wherein synbiotics have been used as therapeutic moiety as well as pharmaceutical carrier for treating various diseases. Highlights: Synbiotics have shown promising effects in various diseases. Synbiotics are more effective than probiotics or prebiotics alone in treating diseases. Restoration of gut microflora is main function of synbiotics. Encapsulation of synbiotics enhances their viability in gastrointestinal tract. Synbiotics have been successfully explored as carrier for pharmaceutical formulations.